(untitled) (BIOPROSPEK: Jurnal Ilmiah Biologi, 2017)
This study was undertaken to investigate the effect of the seed avocado cooking water on lowering blood sugar levels in aloxan-diabetic mouse which has diet of black or red rice. The seed avocado cooking water was administered orally and the blood glucose level was measured weekly for 3 week. The research used a design random complete with 24 male then divided into 6 groups to be treated.The hypoglycaemic activity was evaluated by comparing with the initial blood glucoce level. In aloxan-diabetic mouse, the seed avocado cooking water and diet black or red rice showed their influence to decrease blood sugar levels between 42.72% s.d. 51.06%.The variation of combine the composition diet showed no difference in the effect of a decrease in blood sugar levels